2002
DOI: 10.1163/156853902320387918
|View full text |Cite
|
Sign up to set email alerts
|

Tools and Brains in Birds

Abstract: Tools are traditionally de ned as objects that are used as an extension of the body and held directly in the hand or mouth. By these standards, a vulture breaking an egg by hitting it with a stone uses a tool, but a gull dropping an egg on a rock does not. This distinction between true and borderline (or proto-tool) cases has been criticized for its arbitrariness and anthropocentrism. We show here that relative size of the neostriatum and whole brain distinguish the true and borderline categories in birds usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(105 citation statements)
references
References 74 publications
4
101
0
Order By: Relevance
“…Species differences in general intelligence are likely to extend beyond primates. For example, rooks Corvus frugilegus, members of the large-brained and behaviourally flexible corvid parvorder [37], use tools in captivity but apparently not in the wild [62,63], a finding consistent with the idea that such tool use can result from a generalized cognitive ability.…”
Section: Discussionmentioning
confidence: 68%
“…Species differences in general intelligence are likely to extend beyond primates. For example, rooks Corvus frugilegus, members of the large-brained and behaviourally flexible corvid parvorder [37], use tools in captivity but apparently not in the wild [62,63], a finding consistent with the idea that such tool use can result from a generalized cognitive ability.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have shown that the frequency of feeding innovations is correlated with forebrain size in birds (Lefebvre et al 1997). This result has been extended to include the anatomical correlates of tool use and nesting innovation (Nicolakakis & Lefebvre 2000;Lefebvre et al 2002). Feeding innovations may have ecological implications because introduction success of birds to New Zealand can be predicted by their frequency (Sol & Lefebvre 2000).…”
Section: Introductionmentioning
confidence: 80%
“…In both birds and primates there has been progressive encephalization of the brain in areas that seem to deal with so-called 'intelligent' behaviour . This brain specialization is associated with innovation, social intelligence and tool use (Lefebvre et al 2002;Reader & Laland 2002). Corvus species in particular have relatively large avian brains (Portmann 1947;Lefebvre et al 2002) and are renowned for their considerable social learning abilities (Fritz & Kotrschal 1999;Heinrich 1999) and innovative behaviour (Lefebvre et al 1997(Lefebvre et al , 2002.…”
Section: (D ) Conclusionmentioning
confidence: 99%